The relationship between Health and Labour Force Participation: Evidence from a Panel Data Simultaneous Equation Model - Cai, L (My University, 2007)
A concern when estimating the effect of health on labour supply is that health might be endogenous, and in particular that people might use poor health to justify nonparticipation. This would result in the effect of health being overestimated if health were treated as exogenous. The paper employs a simultaneous equation model to explore the relationship between health and labour force status, allowing for the endogeneity of health. In addition, the paper takes advantage of panel data to control for unobserved heterogeneity so that more efficient estimation results can be obtained than using cross-sectional data. The results confirm the finding in the literature that health has a positive and significant effect on labour force participation for both males and females. As for the reverse effect, it is found that labour force participation has a negative effect on male health but a positive effect on female health, implying that the justification hypothesis is rejected for males but not for females. The exogeneity hypothesis on the health variable is rejected for both samples based on a joint test.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Melbourne Institute Working Papers
Keywords: Health; Employment; Employment -- Labour force participation; Labour market; Employment and unemployment